(untitled) (Вестник КазНУ. Серия Экономическая, 2016)
The article deals with the theory of economic dynamics which are put forward in work of the outstanding scientist – the economist, the classical KeynesianismRoy Forbes Harrod (1900-1978). The urgency and necessity of the logical culmination of the economic theory of the dynamics of R. Harrod justified in his work “Towards a Dynamic Economics” published in 1948. The authors of article attempted for the first time in the state language to show great importance of R. Harrod’s labor in the development of eco-nomic science led him to the global popularity as a leader Keynesian and the founder of the neo-Keynesian theory of the dynamics.